The possibilities of biomass utilization in the field of spatial development - Antal, József; Grasseli, Gábor (Acta Agraria Debreceniensis, 2007)
By joining the European Union, Hungary made a commitment to increasingly utilize renewable energy sources. Keeping in view the agricultural circumstances of Hungary, we can state that biomass utilization has, overall, the greatest range of possibilities to use its products as ‘energy sources’. Biomass raw materials are useful in meeting emission control regulations for environment protection and to reduce climate change. The role of biomass production in spatial and rural development and in rural employment, and also in the decrease of Hungary’s energy dependence, supports development in biomass energy use. My aim in studying biomass utilization is the creation of a micro-regional level, decentralised, agro-energetic system-model for the use of plant and animal biomass for energy purposes, whether naturally or by anthropogenic activity, on agro- and sylvicultural areas, and on animal breeding farms. This model simulation method serves as a planning base for policy-makers during the spatial planning processes. The examination is presently in the stage of data collection. The collection of the basic data of the examination area and the purchase of the necessary equipment, materials and maps has already started. Contact has been made with local stakeholders, municipalities, municipality associations and micro-region managers.